Hubungan Antara Manajemen Pendidikan Profetik Dan Perencanaan Quality Assurance Dengan Sumber Daya Manusia Paripurna - Halimatussa'diyyah Dullah (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2024)
This study aims to determine whether there is a relationship between prophetic education management and quality assurance planning with the development of comprehensive human resources at MTs Darul Hikam, Cirebon City. The research approach used in this study is quantitative, with a correlation research design. The population used by the researcher is a limited population, with a sample of 77 respondents taken using an accidental sampling technique. The data collection technique used in this study is a questionnaire as the main instrument. The results of the study state that: (1) There is a relationship between prophetic education management and the development of comprehensive human resources at MTs Darul Hikam, Cirebon City, based on the t-count value of 6.34 > t-table 1.665, it can be concluded that Ha is accepted while Ho is rejected, with a correlation value of rxy = 0.527, which means that the relationship between the two variables is quite strong. (2) There is a relationship between quality assurance planning and the development of comprehensive human resources at MTs Darul Hikam, Cirebon City, based on the t-count value of 6.22 > t-table 1.665, it can be concluded that Ha is accepted while Ho is rejected, with a correlation value of rxy = 0.582, which means that the relationship between the two variables is quite strong. (3) There is a strong relationship between prophetic education management and quality assurance planning with the development of comprehensive human resources at MTs Darul Hikam, Cirebon City. Based on statistical processing, the significance of the F change value is 0.00, because the Sig. value of 0.00 â‰¤ 0.05, it can be concluded that Ha is accepted while Ho is rejected, with a correlation value of 0.621, which indicates a strong correlation range. These results indicate that the better the prophetic education management and quality assurance planning, the better the comprehensive human resources will be.